1985
DOI: 10.1288/00005537-198510000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Croup and epiglottitis: A radiologic study

Abstract: Because of the controversy regarding the benefits of the lateral neck and chest radiographs in the evaluation of croup and epiglottitis, a two-part retrospective study was initiated. Part I consisted of a retrospective chart review of 44 patients with a final diagnosis of croup and epiglottitis. Part II consisted of the 42 lateral neck and chest x-rays from patients in part I presented to six radiologists who knew only the patients age and the history of respiratory distress. Two hundred forty-six responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Several studies have revealed that sore throat was the commonest presenting complaint. 4,[6][7][8][9][10][11] However, this complaint was nonspecific and commonly expressed by patients with other disease entities. By contrast, odynophagia was more specific to patients with AE and was less often reported in the non-AE group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have revealed that sore throat was the commonest presenting complaint. 4,[6][7][8][9][10][11] However, this complaint was nonspecific and commonly expressed by patients with other disease entities. By contrast, odynophagia was more specific to patients with AE and was less often reported in the non-AE group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that sore throat was the commonest presenting complaint 4 , 6–11 . However, this complaint was nonspecific and commonly expressed by patients with other disease entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, one study showed that lateral radiography only had a sensitivity of 38% and specificity of 76% for diagnosing epiglottitis. 16 An ultrasound of the neck can also demonstrate an increased anteroposterior diameter of the epiglottis in epiglottitis and may aid in diagnosis. 17 Computed tomography is very accurate at diagnosing epiglottitis.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of radiological “thumb sign” should not rule out AE. [5] In a clinically unstable patient with suspected AE, clinical stabilization and airway securement should get priority over X-ray imaging of the neck.…”
mentioning
confidence: 99%